2015
DOI: 10.1615/jpormedia.v18.i6.40
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Double Diffusive Reaction-Convection in an Anisotropic Porous Layer With Internal Heat Source

Abstract: The effect of internal heat source on the onset of double diffusive reaction-convection in an anisotropic porous layer subjected to chemical equilibrium on the boundaries is investigated analytically using linear stability analyses. The linear analysis is based on the usual normal mode method. The Darcy model is employed for the momentum equation. The effect of internal Rayleigh number, Damkohler number, mechanical anisotropy parameter and thermal anisotropy parameter on the stationary and oscillatory convecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They showed that an increase in both the heat source and mass flow results in destabilization. Reviews on internal heat source in porous media can also be found in early studies, [14,15,16,17,18]. There is interest also, in the study of magnetohydrodynamics (MHD) flow and internal heat transfer on the performance of many systems using electrically conducting fluids; for example in geothermal energy extractions and nuclear reactors.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that an increase in both the heat source and mass flow results in destabilization. Reviews on internal heat source in porous media can also be found in early studies, [14,15,16,17,18]. There is interest also, in the study of magnetohydrodynamics (MHD) flow and internal heat transfer on the performance of many systems using electrically conducting fluids; for example in geothermal energy extractions and nuclear reactors.…”
Section: Introductionmentioning
confidence: 99%